2019
DOI: 10.1002/lsm.23105
|View full text |Cite
|
Sign up to set email alerts
|

Surface Processing: An Elegant Way to Enhance the Femtosecond Laser Ablation Rate and Ablation Efficiency on Human Teeth

Abstract: Background and Objectives The employability of the non‐invasive femtosecond laser ablation technique for dental treatment has been severely limited by its low ablation rate despite the advantage of minimal tissue damage. The study explores a means of improving the femtosecond laser ablation rate and efficiency by physiochemical surface modification. Materials and Methods Surface modification of dental hard tissues has been carried out by food graded orthophosphoric acid and Carie care gel pretreatment. The las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For example, Al‐batayneh et al, 34 reported that the laser ablation threshold of primary teeth (200 mJ) is lower than that of permanent teeth (250–350 mJ) due to the variation of chemical composition and microstructure. Also, in our previous study, 26 the demineralized dentin ablates readily at lower ablation threshold fluence (0.48 J/cm 2 ) than healthier dentin (1.50 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…For example, Al‐batayneh et al, 34 reported that the laser ablation threshold of primary teeth (200 mJ) is lower than that of permanent teeth (250–350 mJ) due to the variation of chemical composition and microstructure. Also, in our previous study, 26 the demineralized dentin ablates readily at lower ablation threshold fluence (0.48 J/cm 2 ) than healthier dentin (1.50 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the variation of threshold fluence with % area of dentin tubules can also be explained with the help of defect model and heat accumulation model (Figure 4). According to the defect model, 26,35 the presents of defects on the target surface causes large entrapment of laser light. As a result, the focused laser beam is effectively utilized at the target surface, which in turn reduces the ablation threshold fluence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is worth noting that recently published studies with novel laser systems [32–34] suggest that laser ablation may be used also as an alternative to standard mechanical instrumentation in order to reduce generated debris and smear layer.…”
Section: Discussionmentioning
confidence: 99%